The War between Russia and Georgia – Consequences and Unresolved Questions - Angelika Nußberger (Göttingen Journal of International Law)
The article "The War between Russia and Georgia - Consequences and Unresolved Questions" delivers an examination of the divergent views and legal assesments of the opponents Georgia and Russia with regard to the break-away regions South-Ossetia and Abkhazia. By approaching the conflict from a historical perspective, Prof. Nußberger analyzes whether these regions had the right to secede based on the right to self-determination. Coming to the conclusion that the declarations of independence of South Ossetia and Abkhazia harbor a huge risk for peace and security in the international community and expecially for the (partly displaced) habitants.